(untitled) (Altre Modernità, 2012)
The attention is focused on the cultural and semiotic significance of the area called Rublevka in the outskirts of Moscow. Since the past centuries emperors and dignitaries settled in the woods and on the hills west of the capital because of the clean air and the beauty of the landscape. Soviet party members built their dachas in the same area, confirming the idea of prestige and exclusivness of the territory. In the mid Nineties, just after the fall of the Soviet Union, the so called “new Russian” (nouveaux riches) started to have luxury mansion built along the former Tsar road, nowadays called Rublevka. Moving from the concept of heterotopia, elaborated by Michel Foucault, as space of otherness, which is neither here nor there, that is simultaneously physical and mental, the article investigates the dream of the new Russian leading class of a “paradise” far from the crowd, from the proletarian memories of housing problems in the Soviet Union and the reason why the “aura” of the territory remains the same in spite of historical and social changes. House and mansions were surrounded by high walls and protected by constant patrolling and security cameras. No socialization was intended, and no permeability was allowed. In the last years the traffic jams, caused by security reasons connected with the transit of political leaders (including Putin and Medvedev), are slowly changing the situation. Show business people and entrepreneurs are leaving the area which is turning from a heterotopia into a “super-place”, filled with super markets, luxury stores, infra structures that convinced the pioneers of paradise-settlement that Italian or British countryside is more reliable and more exclusive, and that the outskirts of Moscow are no longer capable of offering “sanctuary” in spite of their secular tradition of prestige.